Pembinaan Masyarakat Berbasis Pesantren Melalui Program Pelatihan Manajemen Qolbu Di Pondok Pesantren Putri Hidayatullah Bojonegoro - Wahidah, Evita Yuliatul (Proceedings of Annual Conference on Community Engagement, 2018)
Community Service is a media to bridge the world of education with society, where universities are faced with the problem of how citizens can face further challenges in the era of globalization. To develop community service activities in a more productive, more structured manner and with more quality results, guidance is made to the students of Putri Hidayatullah Islamic Boarding School in Bojonegoro. This guidance is by implementing the Qalbu management training program to understand yourself, and then want and be able to control yourself after understanding who this is really. And the place to really understand who this is is in the heart, the heart that shows this character and self is actually. This self-made heart is capable of achieving simply because of God. When the heart is clean, clear, and clear, it appears that the whole behavior will reveal cleanliness, cleanliness, clarity and clarity. The appearance of someone is a reflection of his own heart. This guidance is designed using several methods, including: classical methods with the delivery of theory in lectures with variations in discussions in the room, game methods and simulation (out door), and out bonds. The material carried includes ma’rifatullah, ma’rifatur Rosul, ma’rifatul quran, birul wa lidain, ma’rifatun nafs and qolbu management and supported by srana prasana including classrooms, LCD projectors, laptops, equipment and equipment for games and simulations and out bond. Empirically practical, the formation of Putri Hidayatullah Bojonegoro Islamic Boarding School students brought significant changes in improving qolbu management.